(untitled) (Nigerian Journal of Technology, 2016)
The aim of this study is to determine the hydro-power potentials of selected rivers in Edo State using hydrological indices. Four Rivers were investigated namely Ovia, Ikpoba Edion, Orlie Rivers. Discharge measurement was carried out for 12 calendar months, from January 2013 to December 2013 using the grid point technique, commonly known as velocity-area method while Gross Hydropower Potential GHP was determined using model developed by UNIDO. Highest monthly hydropower yields were recorded in September for Ovia, Ikpoba and Edion Rivers and in August for Orlie River. On annual basis, Ovia River, recorded the highest power yield of 61.619MW (suggesting that Ovia river may be suitable for a Medium hydropower scheme, 10MW-100MW) with the highest monthly power yield of 42.381MW recorded in September, followed by August (7.047MW). Lowest power yield of 0.019MW was recorded in February.In Ikpoba River, annual hydropower yield was recorded as 14.78MW, while the lowest power yield of 0.02MW was recorded in April. Highest yield of 5.76MW was recorded in september.River Orlie recorded an annual hydropower yield of 9.819 MW, with August having the highest power yield of 3.296MW. Other significant hydropower yield values were recorded in September and July.Edion River has an annual power yield of 5.49MW. Lowest yield in this river was recorded in April..The dependability of flow for hydropower operations were evaluated using the Flow Duration Curve (FDC). The results showed that extreme high monthly discharge volumes of 544.8m3in Ovia river, 172m3 in Ikpoba river, 102.1m3 in Orlie and 57.1m3 in Edion have dependability percentages of less than 10%. Notwithstanding the hydrological conditions of these rivers can be categorized as adequate (15%-40%) to average moisture conditions (40%-60%). http://dx.doi.org/10.4314/njt.v35i3.26